The local impact of increased numbers of state employees on start-ups in Norway. Issue 3 (27th May 2019) - Stein, Jonas
ABSTRACT: The purpose of the article is to assess the impact of concentrations of state employees on local growth and development. Local multiplier effect theory suggests that the increased local demand for state employees, especially highly skilled employees, would stimulate the local supply of goods and services, and hence local development. However, other theories of regional development have shown that factors such as having a university or city size may also explain why some municipalities with a high percentage of state employees grow faster than others. Following a multilevel panel data analysis of Norwegian municipalities, the author found that the percentage of state employees did not have any effect on local development, measured in terms of the relative number of start-up firms or population growth. While there was a small positive effect of state employees in the bivariate model, state employees did not have a significant effect on local development when controlling for relevant factors such as municipality size or the presence of universities. The author concludes that the relocation of state employees may be a rather limited tool for stimulating local and regional growth and, if applied, policymakers should consider how the relocation could stimulate place-sensitive development in individual municipalities.